Islamic philanthropy and muzakki trust: Mediation of sustainable economic empowerment in Sungai Penuh - Bustami, Bustami; Toni, Hariya; Syafii, Muhammad Hisyam; Azhari, Husain (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study examines the influence of Islamic philanthropy on sustainable economic empowerment and investigates the mediating role of muzakki trust in zakat payers in Sungai Penuh, Jambi, Indonesia. Methodology – A quantitative explanatory design was employed with 160 muzakki recruited through stratified random sampling from the BAZNAS Sungai Penuh registry. Data were analyzed using structural equation modeling (SEM) with IBM AMOS 26.0, incorporating bootstrap mediation analysis with 2,000 resamples. Findings – The findings demonstrate that Islamic philanthropy significantly enhances sustainable economic empowerment both directly and indirectly through muzakki trusts, highlighting trust as a crucial mediating factor in transforming philanthropic resources into impactful outcomes. A strong relationship between philanthropy and trust underscores the importance of institutional credibility, particularly in terms of integrity and Sharia compliance. While community engagement emerges as a key strength, limited access to resources remains a notable constraint. The results also reveal consistent effects across occupational groups, emphasizing the broad applicability of Islamic social finance and the strategic importance of strengthening trust to achieve effective and sustainable empowerment. Implications – Zakat institutions must prioritize transparency, Sharia compliance, and accountability as strategic trust-building mechanisms that amplify the transformative impact of Islamic philanthropic resources on community economic empowerment. Originality – This study pioneers the empirical integration of the theory of planned behavior, social capital theory, and Islamic empowerment theory (tamkin) within a unified structural framework, advancing Islamic social finance scholarship by positioning muzakki trust as a critical institutional bridge between philanthropic inputs and sustainable development outcomes.